Faktor-Faktor yang Berhubungan dengan Pemilihan Pengobatan Tradisional pada Keluarga dalam Mengatasi Masalah Kesehatan Di Kampo Enta Kelurahan Bone Lipu Kabupaten Buton Utara - Mulyani, Sri; Herniwati, Herniwati (Jurnal Gizi Ilmiah, 2016)
Based on the data obtained from the population survey, it was found that from 10 residents who went to traditional medicine only 40% recovered, the rest sought treatment at the puskesmas/hospital because they did not recover. This is a problem for health services because they come in severe conditions. The purpose of this study was to determine the factors associated with the selection of traditional medicine in families in overcoming health problems in Kampo Enta, Bone Lipu Village, North Buton Regency in 2016. This research is a descriptive analytic with a cross sectional study design. The population in this study were all 367 families in Kampo Enta, Bone Lipu Village, North Buton Regency. The sampling technique used is probability sampling. Data analysis using chi square test. Based on the results of the statistical test, the value = 37.804 > = 3.814, it was found that there was a moderate relationship between the knowledge of the head of the family and the choice of traditional medicine. The results of the statistical test obtained a value of = 4.393 > = 3.814, so it is said that there is a weak relationship between belief and the choice of traditional medicine. statistically, the value = 6.270 > = 3.814, it is said that there is a weak relationship between income and the choice of traditional medicine, while based on statistical tests, it is obtained = 5.197 > = 3.814, it is said that there is a weak relationship between the ease of getting services and the selection of traditional medicine in Kampo Enta, Bone Lipu Village, Buton Regency. North of 2016. It is recommended to the local government that it can be used as input for information and consideration in order to determine policies and plans for equitable distri